A social and environmental impact assessment of the Crucitas gold mining project in Costa Rica - Korpela, Daniel (2014)
In 2008 Costa Rica was facing a critical time in its history. A five year mining moratorium had just ended and mining companies were interested in exploring untapped resources in the country. The country was facing important decisions with which development path to take. The Crucitas Mining Project (CMP) was an issue that the whole country had an opinion on; in fact the Constitutional Court of Costa Rica (SALA IV) was debating what to do with the CMP. The purpose of this study was to assist decision makers by providing a well-rounded assessment of the impacts the CMP would have. The goal of this study was to evaluate whether it would be better for Costa Rica to let the mining operation continue or shut it down permanently.